Asthma in adolescence affects daily life and school attendance – Two cross‐sectional population‐based studies 10 years apart. Issue 3 (8th March 2017) - Stridsman, Caroline; Dahlberg, Elisabeth; Zandrén, Karin; Hedman, Linnéa
Abstract: Aim: The aim of this study was to study the impact of asthma on daily life, school absenteeism and physical education. In addition, to describe asthma triggers at school. Design: Two cross‐sectional population‐based studies ten years apart. Method: Within the OLIN‐studies, in 2003 ( n  =   3, 327) and in 2013 ( n  =   2, 345) adolescents (14–15 years) answered an expanded ISAAC questionnaire. Of these, 8% and 11%, respectively with current asthma participated in this study. Results: Between the years 2003–2013, the proportion of adolescents reporting that asthma interfered with daily life had increased, in 2013, girls were significantly more affected than boys. The proportion reporting a worsening of asthma at school had decreased, but it was still over a quarter. The proportion of absenteeism from school and from physical education was at the same level both years. Asthma triggers were described to be poor air quality, poorly cleaned environment, allergens, strong fragrance, rebuilding projects, physical education and stress.